Helga's Dune: 40 years of dune dynamics in the Namib Desert. Issue 4 (14th June 2013) - Besler, Helga; Lancaster, Nicholas; Bristow, Charles; Henschel, Joh; Livingstone, Ian; Seely, Mary; White, Kevin
Abstract The dynamics of a small linear dune on the northern margin of the Namib Sand Sea have been monitored using erosion pins placed at the dune tip since 1969. GPS measurements of these pins enabled estimation of the rates of advance and lateral migration of the dune. The average rate of advance of the dune tip over the period 1969–2012 was 1.99 m yr–1 towards 015°. Rates of advance and lateral movement varied over the period of monitoring, with a decrease in rates of advance by a factor of 50%, but an increase in the rate of lateral movement. Changes in dune behavior appear to be related to changes in wind regime and the vegetation cover of the interdune area, as a result of increased rainfall in recent years. This study demonstrates the dynamic nature of the tip of this dune and its sensitivity to changes in winds and sand supply.